Edible seaweed as future functional food: Identification of α-glucosidase inhibitors by combined use of high-resolution α-glucosidase inhibition profiling and HPLC–HRMS–SPE–NMR. (15th July 2016) - Liu, Bingrui; Kongstad, Kenneth T.; Wiese, Stefanie; Jäger, Anna K.; Staerk, Dan
Highlights: Nineteen seaweeds were screened for antioxidant and α-glucosidase inhibitory activity. Active extracts investigated by high-resolution α-glucosidase inhibition profiling. HPLC–HRMS–SPE–NMR used for structure elucidation of α-glucosidase inhibitors. α-Glucosidase inhibitory activity caused by phlorotannins as well as fatty acids. Oleic-, linoleic- and eicosapentaenoic acid showed IC50 of 0.069, 0.075 and 0.10 mM. Abstract: Crude chloroform, ethanol and acetone extracts of nineteen seaweed species were screened for their antioxidant and α-glucosidase inhibitory activity. Samples showing more than 60% α-glucosidase inhibitory activity, at a concentration of 1 mg/ml, were furthermore investigated using high-resolution α-glucosidase inhibition profiling combined with high-performance liquid chromatography–high-resolution mass spectrometry–solid-phase extraction–nuclear magnetic resonance spectroscopy (HR-bioassay/HPLC–HRMS–SPE–NMR). The results showed Ascophyllum nodosum and Fucus vesicolosus to be rich in antioxidants, equaling a Trolox equivalent antioxidant capacity of 135 and 108 mM Trolox mg −1 extract, respectively. HR-bioassay/HPLC–HRMS–SPE–NMR showed the α-glucosidase inhibitory activity of A. nodosum, F. vesoculosus, Laminaria digitata, Laminaria japonica and Undaria pinnatifida to be caused by phlorotannins as well as fatty acids – with oleic acid, linoleic acid and eicosapentaenoic acid being the most potent with IC50 values of 0.069, 0.075 and 0.10 mM, respectively, and showing a mixed-type inhibition mode.